Revitalisasi Objek Wisata Pantai Kualo Kecamatan Muara Bangkahulu Kota Bengkulu - Mirna Yunita; Edwar Edwar (Universitas Prof. Dr. Hazairin, S.H, 2017)
The background is not optimum management of coastal attractions qualo than other tourist attractions in the city of bengkulu so that the impact on the lack of interest tourists to visit opbjek this wisara and this impact also on the absence of PAD from this tourism activity. The purpose of this research is to formulate alternative development strategy in order to revitalize coastal beach attractions. The type of this research is descriptive qualitative conducted at the Department of Tourism and Culture of Bengkulu City, Muara Bangkahulu District, Society and tourists. Determination of informants conducted Purposive. Data collection is done through obervasi, interview, and documentation. Data management is done through SWOT analysis. The results can be formulated eight development strategies that must be done by the government.